2009
DOI: 10.1016/j.jss.2008.07.027
|View full text |Cite
|
Sign up to set email alerts
|

Differential Regulation of Aortic Growth in Male and Female Rodents Is Associated With AAA Development

Abstract: Background The objective was to examine effects of gonadal hormone manipulation on aortic diameter and macrophage infiltration in rodents during abdominal aortic aneurysm (AAA) formation. Methods Experiment 1: 17-β estradiol and testosterone pellets were implanted in male (ME) and female (FT) rats. No pellet was implanted in shams (MES, FTS). Experiment 2: Testes and ovaries were removed from males (MO) and females (FO), respectively. No organs were removed from shams (MOS, FOS). Experiment 3: Male and femal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
51
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 47 publications
(55 citation statements)
references
References 41 publications
4
51
0
Order By: Relevance
“…In addition, they demonstrated that exogenous estrogens have prominent protective effects, as castrated females treated with 17b-estradiol presented smaller AAAs and lower macrophage counts compared to only castrated females. 69 Wu et al 70 found SMCs disorganization, inflammatory cell infiltration, partial elastic fiber degradation, larger aneurysm size, and increased MMP2 and MMP9 mRNA levels in ovariectomized female rats, illustrating also the anti-inflammatory/antiproteolytic effects of estrogen in the elastase-induced AAA model. On the other hand, Henriques et al 75 showed that murine ovariectomy failed to significantly modify neither the incidence nor the severity of the AngII-induced AAAs, indicating that the endogenous ovarian hormones are not the primary mediators of sex differences in AngII-induced AAA.…”
Section: The Effect Of Castration On Aaa Parametersmentioning
confidence: 98%
See 3 more Smart Citations
“…In addition, they demonstrated that exogenous estrogens have prominent protective effects, as castrated females treated with 17b-estradiol presented smaller AAAs and lower macrophage counts compared to only castrated females. 69 Wu et al 70 found SMCs disorganization, inflammatory cell infiltration, partial elastic fiber degradation, larger aneurysm size, and increased MMP2 and MMP9 mRNA levels in ovariectomized female rats, illustrating also the anti-inflammatory/antiproteolytic effects of estrogen in the elastase-induced AAA model. On the other hand, Henriques et al 75 showed that murine ovariectomy failed to significantly modify neither the incidence nor the severity of the AngII-induced AAAs, indicating that the endogenous ovarian hormones are not the primary mediators of sex differences in AngII-induced AAA.…”
Section: The Effect Of Castration On Aaa Parametersmentioning
confidence: 98%
“…64 The protective effects of estrogens were confirmed by other studies. 69,70 Additionally, Martin-McNultry et al 71 demonstrated that infusion of AngII induced AAA in 90% of Apoe À/À mice, whereas with 17b-estradiol treatment, only 42% of mice developed AAAs. In another AAA study, tamoxifen, a selective estrogen receptor modulator, decreased neutrophil infiltration and increased catalase expression.…”
Section: Exogenous Estrogens In Aaamentioning
confidence: 99%
See 2 more Smart Citations
“…There have been several studies from our lab utilizing the elastase perfusion model demonstrating that females are protected from AAA formation 2,3,4,5 . The mechanisms underlying this gender difference are not completely clear.…”
Section: Introductionmentioning
confidence: 99%